Leptomeningeal melanomatosis associated with neurocutaneous melanosis: An autopsy case report. (17th December 2014) - Matsumura, Mai; Okudela, Koji; Tateishi, Yoko; Umeda, Shigeaki; Mitsui, Hideaki; Suzuki, Takehisa; Nakayama, Takashi; Inayama, Yoshiaki; Ohashi, Kenichi
<x xml:space="preserve">Abstract</x> An autopsy case of leptomeningeal melanomatosis associated with neurocutaneous melanosis (NCM) involving a 44‐year‐old male is reported. The autopsy showed that the leptomeningeal surface of the brain and the spinal cord were covered with a diffuse black lesion. A histological examination detected diffusely distributed, proliferating, melanin‐containing cells and demonstrated that the lesion consisted of three different components; i.e. regions of melanomatosis, melanocytosis, and melanocyte hyperplasia. In the leptomeningeal melanomatosis component, tumor cells with pleomorphic nuclei and prominent nucleoli had infiltrated into the cerebral parenchyma via Virchow–Robin spaces. The Ki‐67 labeling index and the nuclear accumulation of p53 and p16 protein were immunohistochemically examined in each component. The Ki‐67 labeling indices of the melanomatosis, melanocytosis, and melanocyte hyperplasia components were 8.7%, 0.8%, and 0%, respectively. Immunostaining of nuclear p16 produced a negative result in the melanomatosis component, but positive results in the melanocytosis and melanocyte hyperplasia components, whereas nuclear p53 expression was not detected in any of the components. This case suggests that p16INK4/CDKN2 may play a significant role in progression of leptomeningeal melanocytic neoplasms. We also reviewed previously reported cases of leptomeningeal neoplasms associated with NCM and discussed the relationship between the biological behavior and proliferative activity of such lesions.